Analysis of Prediagnostic Circulating Levels of Gonadotropins and Androgens with Risk of Epithelial Ovarian Cancer - Parchwani, Deepak; Dholariya, Sagar Jayantilal; Takodara, Sohil; Singh, Ragini; Sharma, Vivek Kumar; Saxena, Alpana; Patel, Digishaben D.; Radadiya, Madhuri (Journal of Laboratory Physicians, 2022)
Background Prevailing experimental and epidemiological evidence supports the role of circulating endogenous sex steroid hormones in the pathogenesis of ovarian carcinogenesis by dysregulation of cell differentiation, proliferation, and apoptosis but is scarce and inconclusive.Objectives This article evaluates the role of circulating levels of gonadotropins (follicle-stimulating hormone [FSH], luteinizing hormone [LH]) and androgens (testosterone, dehydroepiandrosterone-sulfate [DHEA-S]) for the risk of epithelial ovarian cancer in a case–control approach using samples collected in advance of clinical diagnosis.Materials and Methods A total of 100 epithelial ovarian cancer (EOC) patients and 100 healthy female controls were consequently enrolled in this hospital-based case–control study. Serum FSH, LH, testosterone, and DHEA-S were measured based on the principle of electrochemiluminescence immunoassay. Suitable descriptive statistics were used for different variables.Results Median values of FSH (58.9 vs. 45.5 IU/L, p = 0.02) and DHEA-S (163.43 vs. 142.2 ug/dL, p = 0.03) were significantly high in EOC patients compared with controls. Conditional logistic regression was used to estimate the odds ratio (OR) across increasing thirds of FSH and DHEA-S concentrations, and the results revealed that the highest third tertile of FSH (> 72.6 IU/L; OR = 3.0, confidence interval [CI] = 1.24–7.29, p trend = 0.04) and DHEA-S (> 194.2 ug/dL; OR = 3.8, CI = 1.26–11.61, p trend = 0.03) were significantly associated with increased risk of ovarian cancer in postmenopausal and premenopausal women, respectively. The statistically significant trend observed for FSH in postmenopausal women, remained only for the subgroup with menopause duration greater than 10 years (OR = 5.9, CI = 1.33–26.66, p trend = 0.04). FSH and DHEA-S concentrations and ovarian cancer risk were internally consistent with groups defined by oral contraceptive pill use, hormone replacement therapy, and smoking. However, no evidence was found for the association between serum LH and testosterone level with the occurrence of ovarian tumorigenesis.Conclusion Prediagnostic circulating concentration of FSH and DHEA-S unveiled a significant positive association with augmented risk of EOC, thus might serve as a predictive marker for the susceptibility to ovarian carcinogenesis and should be added in the screening profile of EOC for early recognition and scheduling necessary interventions/management strategies.
Keywords: epithelial ovarian cancer; follicle-stimulating hormone; dehydroepiandrosterone-sulfate